Ascorbic acid-mediated reductive disassembly of Fe3+-tannic acid shells in degradable single-cell nanoencapsulation. Issue 89 (1st October 2020) - Lee, Hojae; Park, Joohyouck; Han, Sang Yeong; Han, Sol; Youn, Wongu; Choi, Hyunwoo; Yun, Gyeongwon; Choi, Insung S.
Abstract : The simple use of vitamin C leads to the reductive disassembly of the Fe 3+ -TA complex and in situ artificial shell degradation in single-cell nanoencapsulation. Abstract : Rapid degradation of Fe 3+ -tannic acid films is achieved under mild conditions via ascorbic acid-mediated Fe 3+ reduction, which overcomes the problems in the disassembly of a metal–organic complex including slow reaction rates and reaction incompatibility with living cells. The strategy of reductive disassembly is applied to degradable single-cell nanoencapsulation, providing an advanced tool for tightly controlling and manipulating the cell–material interface.